Attosecond and nano-Coulomb electron bunches via the Zero Vector Potential mechanism - Timmis, RJL; Paddock, RW; Ouatu, I; Lee, J; Howard, S; Atonga, E; Ruskov, RT; Martin, H; Wang, RHW; Aboushelbaya, R; Leyen, MWVD; Gumbrell, E; et al. (Springer Nature, 2024)
The commissioning of multi-petawatt class laser facilities around the world is gathering pace. One of the primary motivations for these investments is the acceleration of high-quality, low-emittance electron bunches. Here we explore the interaction of a high-intensity femtosecond laser pulse with a mass-limited dense target to produce MeV attosecond electron bunches in transmission and confirm with three-dimensional simulation that such bunches have low emittance and nano-Coulomb charge. We then perform a large parameter scan from non-relativistic laser intensities to the laser-QED regime and from the critical plasma density to beyond solid density to demonstrate that the electron bunch energies and the laser pulse energy absorption into the plasma can be quantitatively described via the Zero Vector Potential mechanism. These results have wide-ranging implications for future particle accelerator science and associated technologies.